Analisis dan Pemetaan Potensi Daerah Berbasis GIS Dengan Menggunakan Metode MRP (Material Requirement Planning) - Julian Chandra Wibawa; Rizki Zulfikar (Maranatha University Press, 2017)
Regional economic development is largely determined by the regional policy itself in determining sectors that are prioritized for economic growth in the area. Efforts taken by the Local Government in order to develop the potential of strategic sectors is to create a GIS-based management information system capable of analyzing any economic base sector that can promote economic growth in the district and economic sectors of any potential competitive competitiveness and comparative to Bandung Regency, producing typology of each region based on its potential. Not only by providing information that has been indicated, but also requires a more konpherensif information that supports the development of regional potential so that potential investors or the public to get information that is really accurate. Some of the methods used for the study of the literature conducted with the aim to obtain data and information related to the basic concept of Management Information System Potential Areas Based on GIS to facilitate the process of obtaining the required data, it is necessary to compile a method of collecting data that is comprehensive and structured so as to utilize the time provided by creating a listing of data needs. Then the system design methods that include the concept of database design, software architecture design, model design for application and application testing methods.